PENGETAHUAN MASYARAKAT DESA HUTATONGA KECAMATAN PANYABUNGAN BARAT TENTANG PERBANKAN SYARIAH - isa, muhammad (Institut Agama Islam Negeri Padangsidimpuan, 2017)
Hutatonga is a small village in West Panyabungan, Mandailing Natal Regency. It’s citizens are moslem (100%), but majority of them are usually transaction with conventional banks, not islamic banks. This fact is opposite with their religion tenets. This research aim to measure their knowledge about Islamic Bank. This research result shows that majority of them know that there are islamic bank offices in Mandailing Natal Regency, but they don’t understand what is it islamic bank, it’s products and services, and it’s differences with conventional bank.